Kinetic mixing in models with an extra Abelian gauge symmetry - Tran, Hieu Minh (Communications in Physics, 2018)
The Lagrangian of a theory possessing two Abelian gauge symmetries may contains a gauge kinetic mixing term without violating any known symmetries. In this paper, the formulation of theories extended by an additional Abelian gauge symmetry in the superfield formalism is presented. By rotating in the space of the gauge fields, the gauge kinetic mixing term can be eliminated, and the relevant charge and coupling are shifted in comparison with the original quantities. This process is valid for both theories with or without supersymmetry. We demonstrate, for example, the effect of the gauge kinetic mixing term in  the case of the U(1) extension of the minimal supersymmetric standard model. Various physical observables are computed for a given benchmark point. We find that the gauge kinetic mixing is important for the model to predict the observables in a good agreement with experimental data.